(untitled) (Cardiovascular Journal, 2020)
Background: Diabetes mellitus is an independent risk factor for coronary artery disease and it adversely affects the postoperative outcome after CABG surgery. Adequate control of diabetes for a longer period, which can be assessed by HbA1c, before OPCAB may reduce development of postoperative atrial fibrillation and thus improve outcome. Methods: This was an observational study included sixty diabetic patients purposively who underwent isolated off pump coronary artery bypass procedure in NICVD. Total sample contained 60 diabetic patients, which were divided in two equal groups. Grouping was Group I – 30 Diabetic patients with preoperative HbA1c <7% and Group II – 30 Diabetic patients with preoperative HbA1c ≥7% and all of whom underwent isolated OPCAB. Postoperative atrial fibrillation and other complications were recorded and compared in two groups of patients. Results: Most postoperative atrial fibrillation (AF) developed in higher age group 61-70 years (61.5%). Postoperative complications were higher in group II. Postoperative AF was significantly higher in diabetic patients having preoperative HbA1c ≥7% compare to diabetic patients with HbA1c <7% in early postoperative period after OPCAB. Age (61-70 years) (OR=1.872, p=0.018), preoperative HbA1c ≥7% (OR=19.029, p=0.002) and hypertension (OR=1.091, p=0.019) was found significantly associated with increased development of postoperative atrial fibrillation. Conclusion: Our study revealed that higher preoperative HbA1c level was associated with increased incidence of new onset atrial fibrillation after OPCAB. So, it can be used as a reliable indicator for adequate control of diabetes preoperatively among patients selected for isolated elective OPCAB in future. Cardiovasc. j. 2020; 12(2): 113-119